ANGUSTIFOLIA negatively regulates resistance to Sclerotinia sclerotiorum via modulation of PTI and JA signalling pathways in Arabidopsis thaliana. (15th April 2022) - Gao, Xiuqin; Dang, Xie; Yan, Fengting; Li, Yuhua; Xu, Jing; Tian, Shifu; Li, Yaling; Huang, Kun; Lin, Wenwei; Lin, Deshu; Wang, Zonghua; Wang, Airong
Abstract: Sclerotinia sclerotiorum is a devastating pathogen that infects a broad range of host plants. The mechanism underlying plant defence against fungal invasion is still not well characterized. Here, we report that ANGUSTIFOLIA (AN), a CtBP family member, plays a role in the defence against S. sclerotiorum attack. Arabidopsis an mutants exhibited stronger resistance to S. sclerotiorum at the early stage of infection than wild‐type plants. Accordingly, an mutants exhibited stronger activation of pathogen‐associated molecular pattern (PAMP)‐triggered immunity (PTI) responses, including mitogen‐activated protein kinase activation, reactive oxygen species accumulation, callose deposition, and the expression of PTI‐responsive genes, upon treatment with PAMPs/microbe‐associated molecular patterns. Moreover, Arabidopsis lines overexpressing AN were more susceptible to S. sclerotiorum and showed defective PTI responses. Our luminometry, bimolecular fluorescence complementation, coimmunoprecipitation, and in vitro pull‐down assays indicate that AN interacts with allene oxide cyclases (AOC), essential enzymes involved in jasmonic acid (JA) biosynthesis, negatively regulating JA biosynthesis in response to S. sclerotiorum infection. This work reveals AN is a negative regulator of the AOC‐mediated JA signalling pathway and PTI activation. Abstract : ANGUSTIFOLIA negatively regulates plant immunity against biotrophic and necrotrophic pathogens by activating broad PTI responses, such as ROS burst, MAPK activation, and callose deposition, by interacting with allene oxide cyclases.